If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13b + -1 = 11 + -2x Reorder the terms: -1 + 13b = 11 + -2x Solving -1 + 13b = 11 + -2x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 13b = 11 + 1 + -2x Combine like terms: -1 + 1 = 0 0 + 13b = 11 + 1 + -2x 13b = 11 + 1 + -2x Combine like terms: 11 + 1 = 12 13b = 12 + -2x Divide each side by '13'. b = 0.9230769231 + -0.1538461538x Simplifying b = 0.9230769231 + -0.1538461538x
| 2l+2w=72 | | -6+g=-11 | | 9.3x=139.5 | | 3x-5y=-1 | | 56.84-2.51= | | 5(x-2)+58=-3x | | 3(w+3)-4(w+5)=0 | | -4x+12=-4 | | 12=-3x+12 | | 6x-3x= | | 2x=-8+2x+10 | | .25q+.10d=4.95 | | 6x+7(4x-7)=155 | | 12x-7+8x-13= | | 2(X^2+X-30)=0 | | 5n+8d=180 | | 6y=-3x+12 | | x^2+14x-60=0 | | 3n+4d=440 | | 12x-10y=-2 | | -6x-11=3x+16 | | 4s+7l=287 | | 8x+4=6x-5+x | | 2x+3y=68 | | -31*-4= | | 4+7a=60 | | x^2+x+67=0 | | a=7t+100 | | x+12=6x-13 | | x^2+x+67=x^2+x+2 | | 8x+8=7x-1 | | 20+5p=75 |